Stabilized aqueous composition based on blocked calcium silicate cement for initiating the setting and hardening of aluminous cement compositions
Patent Information
- Application Number
- JP2024551668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2023-02-28
- Publication Date
- 2025-03-13
Smart Images

Figure 2025506911000001 
Figure 2025506911000002 
Figure 2025506911000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a long-term stabilized aqueous initiator composition for initiating the setting and hardening of an alumina cement composition. In particular, the long-term stabilized aqueous initiator composition comprises a blocked calcium silicate cement and water. Furthermore, the present invention relates to a method for preparing the long-term stabilized aqueous initiator composition and to the use of said composition in a system for chemically fixing fastening means, preferably metal elements, in mineral substrates such as masonry, concrete, permeable concrete, or structures made of natural stone. [Background technology]
[0002] Aqueous compositions, especially aqueous suspensions, are heterogeneous mixtures containing solid particles large enough for settling and more or less in the form of a fluid or paste. The advantage of such suspensions is that they form ready-to-use solutions that can be used directly for any application for construction chemistry, such as chemical fixing of fastening means, preferably metal elements such as anchor rods, especially threaded rods, bolts, steel reinforcements, in recesses such as boreholes in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone.
[0003] When fast curing is desired, organic systems based on free radically polymerizable resins are used, however such systems are generally known to be polluting, expensive, potentially dangerous and / or toxic to the environment and to those who handle them, and they often need to be specially labeled.
[0004] To overcome these shortcomings, mainly mineral systems based on alumina cement have been developed. Alumina cement has monocalcium aluminate as its main component and is widely used in the building and construction industry because the final product shows a high level of mechanical performance over time. Alumina cement is also resistant to bases, achieves maximum strength more quickly than Portland cement, and can withstand solutions of sulfates. Therefore, alumina cement systems are preferably used in the field of chemical fixation.
[0005] In particular, there are many two-component mortar systems, sometimes referred to as kit-of-parts, in which the components are mixed before use or during application to initiate the curing process and are intended to provide good chemical fixation of the anchoring means in the mineral matrix: one component provides the stabilized cementitious composition, and then another component initiates its setting and hardening.
[0006] Additives for the setting and hardening of aluminous cements are known from the prior art, for example in US Patent No. 3,826,665 an adjuvant composition for improving the setting and hardening properties of aluminous cements is described.
[0007] DE 2311239 describes an adjuvant composition for improving the setting and hardening properties of alumina cements and mortars, comprising lithia, a water-soluble lithium salt, and a hydroxylated organic acid or its salt or ester. The fluid may be directly incorporated into the alumina cement or into the mortar and concrete during their manufacture or added to the mixing water during application. However, a drawback of this system is that the activator composition cannot be stored for a sufficient time to be ready for use, and therefore must be freshly prepared before use depending on the desired setting and hardening time, resulting in more procedural steps before application. In addition, the lithium-based activator components are expensive, their extraction is problematic from a humanitarian, economic and political point of view, and has a high carbon footprint.
[0008] When it comes to chemically fixing an anchoring means to a mineral substrate, a rapid curing time, i.e. less than 5 minutes, is not always desirable. Moreover, most of the known systems lack sufficient fluidity for most practical applications of the resulting compositions. In many cases, such prior art compositions also show a tendency to crack after a relatively short time or do not exhibit the necessary mechanical performance even under the effect of elevated temperatures. Moreover, these systems cannot be stored for long periods of time before use.
[0009] Therefore, there is a need for a long-term stabilized aqueous initiator composition for initiating the setting and hardening of alumina cement compositions, which is superior to the systems of the prior art in terms of environmental aspects, health and safety, handling, storage time, and a good balance between the setting and hardening of the mortar upon application.Furthermore, it is of interest to provide a long-term stabilized aqueous initiator composition that can be used in a multi-component system for chemically fixing anchoring means in mineral substrates without adversely affecting the handling, characteristics, and mechanical performance of the chemical anchoring system.Furthermore, it is of interest to reduce the water-to-cement ratio and conversion used in the system, which leads to a decrease in performance over time.
[0010] In view of the above, it is an object of the present invention to provide a long-term stabilized aqueous initiator composition that overcomes the shortcomings of the compositions of the prior art, in particular, a long-term stabilized aqueous initiator composition that is ready to use, easy to handle, environmentally friendly, can be stably stored for a period of time before use, exhibits a good balance between setting and hardening, still provides good mechanical performance of the system in terms of chemically fixing the anchoring means even under the effect of elevated temperatures during application, and reduces the water to cement ratio and conversion used in the system.
[0011] It is further an object of the present invention to provide a method for preparing a long-term stabilized aqueous initiator composition that can be used in multi-component systems, is cost-effective, environmentally friendly, simple to implement, and results in a stable, easy to apply aqueous initiator composition.
[0012] In addition, it is an object to provide a method for activating the setting and hardening of cured aqueous phase aluminous cement components that is easy to carry out and results in a chemical fixation that can be used in the field of chemical fixing of fixing means in mineral substrates.
[0013] It is further an object of the present invention to provide a long-term stabilized aqueous initiator composition which can be used in multi-component systems, especially two-component systems, for the chemical fixation of anchoring means, preferably metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone.
[0014] These and other objects which will become apparent from the ensuing description of the invention are solved by the invention as set forth in the independent claims. The dependent claims relate to preferred embodiments.
[0015] Summary of the Invention In one aspect, the present invention provides a long-term stabilized aqueous initiator composition for initiating the setting and hardening of an alumina cement composition, which is stable over a period of time at room and elevated temperatures. In particular, the long-term stabilized aqueous initiator composition comprises a blocked calcium silicate cement and water.
[0016] In another aspect, the present invention provides a method for preparing the long-term stabilized aqueous initiator composition.
[0017] In yet another aspect, the present invention provides a method for activating the setting and hardening of a cured aqueous phase aluminous cement component using the long-term stabilized aqueous initiator composition.
[0018] In yet another aspect, the present invention provides a long-term stabilized aqueous initiator composition that can be used in multi-component systems, especially two-component systems, for the chemical fixation of anchoring means, preferably metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The following terms and definitions are used in the context of the present invention.
[0020] As used in the context of the present invention, the singular forms "a" and "an" also include the respective plural forms unless the context clearly dictates otherwise. Thus, the terms "a" or "an" are intended to mean "one or more" or "at least one," unless otherwise specified.
[0021] The term "aluminous cement" in the context of the present invention refers to calcium aluminate cement, consisting mainly of hydrated active calcium aluminate. Another name is "high aluminous cement" or "Ciment fondu" in French. The main active ingredient of calcium aluminate cement is monocalcium aluminate (CaAl2O4, CaO·Al2O3, or CA in cement chemical notation).
[0022] The term "shelf life" in the context of the present invention refers to the time that a component remains in the form of an approximately fluid, aqueous composition of a solid product that can be converted back into an aqueous composition by mechanical means without setting or losing its reactivity.
[0023] The term "initiator" in the context of the present invention refers to a compound or composition that modifies the chemical environment to initiate a specific chemical reaction. In the present invention, the initiator modifies the pH value of the mortar composition, thereby deblocking the hydraulic binder in the final mixture.
[0024] The term "binder" or "binder component" in the context of the present invention refers to the calcium-aluminate based cementitious component and other additional optional components such as, for example, fillers. In particular, the term "main binder component" refers to component A.
[0025] The term "siliceous clinker phase" refers to the clinker phases of ordinary Portland cement clinker, tricalcium silicate C3S or dicalcium silicate C2S, or mixtures thereof, and thus the siliceous clinker phase is essentially free of aluminate clinker phases and is free of lime.
[0026] The term "stable" or "stabilized" in the context of the present invention means that the viscosity and pH value of the aqueous initiator composition do not change significantly during storage and the composition does not coagulate or harden.
[0027] The term "long-term stabilized aqueous initiator composition" in the context of the present invention is also referred to as component B for two-component mortar systems.
[0028] The term "water to cement ratio" in the context of the present invention refers to the ratio of (water) to (calcium aluminate cement and siliceous clinker phases), i.e. water / CAC+C2S, or water / CAC+C3S, or water / CAC+C2S+C3S.
[0029] Surprisingly, the inventors have found that the long-term stable aqueous initiator composition based on blocked calcium silicate cement can be used to activate aqueous slurries containing blocked alumina components as the main binder component in inorganic mortar systems.
[0030] While typical calcium aluminate-based binders rely on synthetic or mined carbonate sources to mitigate strength loss due to conversion phenomena, calcium silicate cement can be used as a binder. By blocking calcium silicate cement with sugars such as gluconate or glucose in water, an alkaline pH is achieved that can be used to activate the blocked calcium aluminate cement components. Thus, a separate activator such as sodium hydroxide or lithium hydroxide is not required. The alkaline pH generated from the hydration of calcium aluminate cement subsequently activates the calcium silicate cement.
[0031] The present invention relates to a long-term stabilized aqueous initiator composition comprising a blocked calcium silicate cement and water.
[0032] The blocked calcium silicate cement of the long-term stabilized aqueous initiator composition includes a calcium silicate cement and a blocking agent.
[0033] In particular, the blocked calcium silicate cement comprises the siliceous clinker phase tricalcium silicate C3S, dicalcium silicate C2S or a mixture thereof, preferably the blocked calcium silicate cement is tricalcium silicate C3S or dicalcium silicate C2S. In the most preferred embodiment, the calcium silicate cement is aluminate clinker phase-free and lime-free tricalcium silicate C3S or dicalcium silicate C2S, most preferably aluminate clinker phase-free and lime-free tricalcium silicate C3S.
[0034] The long-term stabilized aqueous initiator composition of the present invention comprises at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 20% by weight, and most preferably at least about 30% by weight, about 5% to about 95% by weight, preferably about 10% to about 90% by weight, more preferably about 20% to about 80% by weight, and most preferably about 30% to about 75% by weight of calcium silicate cement, based on the total weight of the long-term stabilized aqueous initiator composition.
[0035] The blocking agent for calcium silicate cement is selected from the group consisting of monosaccharides, carboxylic acids, gluconic acid, glycolic acid, lignosulfonates, phosphoric and phosphonic acids, their salts and esters, glucose, and mixtures thereof, preferably glucose or sodium gluconate, most preferably sodium gluconate.
[0036] The long-term stabilized aqueous initiator composition comprises at least about 0.01% by weight, preferably at least about 0.05% by weight, more preferably at least about 0.1% by weight, and most preferably at least about 1.0% by weight, from about 0.01% to about 25% by weight, preferably from about 0.05% to about 20% by weight, more preferably from about 0.1% to about 15% by weight, and most preferably from about 1.0% to about 10% by weight of the blocking agent, based on the total weight of Component B. In a most preferred embodiment, Component B comprises from about 0.01 to about 0.4% by weight of sodium gluconate, based on the total weight of the long-term stabilized aqueous initiator composition.
[0037] The ratio of blocking agent:C3S is preferably 1:300, more preferably 1:500, and most preferably 1:1000.
[0038] The water content in the long-term stabilized aqueous initiator composition is at least about 1% by weight, preferably at least about 5% by weight, more preferably at least about 10% by weight, and most preferably at least about 20% by weight, from about 1% to about 60% by weight, preferably from about 5% to about 50% by weight, more preferably from about 10% to about 40% by weight, and most preferably from about 15% to about 30% by weight, based on the total weight of the long-term stabilized aqueous initiator composition.
[0039] In advantageous embodiments, the long-term stabilized aqueous initiator composition further comprises the following properties, either alone or in combination:
[0040] The long-term stabilized aqueous initiator composition may further comprise a thickener. The thickener used in the present invention may be selected from the group consisting of bentonite, silicon dioxide, quartz, acrylate-based thickeners such as alkali-soluble or alkali-swellable emulsions, fumed silica, clays, and titanate chelating agents. Mention may be made by way of example of polyvinyl alcohol (PVA), hydrophobically modified alkali soluble emulsion (HASE), hydrophobically modified ethylene oxide urethane polymers known in the art as HEUR, and cellulosic thickeners such as hydroxymethyl cellulose (HMC), hydroxyethyl cellulose (HEC), hydrophobically-modified hydroxy ethyl cellulose (HMHEC), sodium carboxymethyl cellulose (SCMC), sodium carboxymethyl 2-hydroxyethyl cellulose, 2-hydroxypropyl methylcellulose, 2-hydroxyethyl methylcellulose, 2-hydroxybutyl methylcellulose, 2-hydroxyethyl ethylcellulose, 2-hydroxypropyl cellulose, attapulgite clays, and mixtures thereof. Suitable thickeners are commercially available products such as Optigel WX (BYK-Chemie GmbH, Germany), Rheolate 1 (Elementis GmbH, Germany), and Cellosize™, Acrysol ASE-60 (The Dow Chemical Company).The long-term stabilized aqueous initiator composition comprises at least about 0.01 wt. %, preferably at least about 0.05 wt. %, more preferably at least about 0.1 wt. %, and most preferably at least about 0.3 wt. %, from about 0.01 wt. % to about 15 wt. %, preferably from about 0.05 wt. % to about 10 wt. %, more preferably from about 0.1 wt. % to about 5 wt. %, and most preferably from about 0.1 wt. % to about 1 wt. %, of the thickener, based on the total weight of the long-term stabilized aqueous initiator composition.
[0041] The long-term stabilized aqueous initiator composition may optionally contain at least one mineral filler. The mineral filler that may be used in the present invention may be limestone filler, such as calcite, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick powder, rice husk ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof. Suitable fillers are commercially available products. The long-term stabilized aqueous initiator composition may contain at least about 1 wt. %, preferably at least about 10 wt. %, more preferably at least about 20 wt. %, and most preferably at least about 30 wt. % of said at least one filler, based on the total weight of the long-term stabilized aqueous initiator composition. The at least one mineral filler contained in the long-term stabilized aqueous initiator composition according to the present invention is preferably a mixture of mineral fillers.
[0042] The long-term stabilization aqueous initiator composition can also include a plasticizer. The plasticizer may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the family of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika™ ViscoCrete™-20 HE (Sika, Germany). Suitable plasticizers are commercially available products. Component B may comprise at least about 0.2 wt. %, preferably at least about 0.3 wt. %, more preferably at least about 0.4 wt. %, and most preferably at least about 0.5 wt. %, from about 0.2 wt. % to about 20 wt. %, preferably from about 0.3 wt. % to about 15 wt. %, more preferably from about 0.4 wt. % to about 10 wt. %, and most preferably from about 0.5 wt. % to about 5 wt. % of the plasticizer, based on the total weight of the long-term stabilized aqueous initiator composition.
[0043] The presence of plasticizers and thickeners does not change the overall inorganic nature of the present long-term stabilized aqueous initiator composition.
[0044] Furthermore, the long-term stabilized aqueous initiator composition, when used as an initiator for the alumina cement component, may include an accelerator component. The accelerator component is composed of at least one alkali and / or alkaline earth metal salt selected from the group consisting of hydroxides, chlorides, sulfates, phosphates, monohydrogen phosphates, dihydrogen phosphates, nitrates, carbonates, and mixtures thereof, preferably the accelerator component is an alkali or alkaline earth metal salt, more preferably a water-soluble alkali or alkaline earth metal salt, more preferably a calcium metal salt such as calcium hydroxide, calcium sulfate, calcium carbonate, calcium chloride, calcium formate, or calcium phosphate, a sodium metal salt such as sodium hydroxide, sodium sulfate, sodium carbonate, sodium chloride, sodium formate, or sodium phosphate, or a lithium metal salt such as lithium hydroxide, lithium sulfate, lithium sulfate monohydrate, lithium carbonate, lithium chloride, lithium formate, or lithium phosphate, and most preferably lithium sulfate or lithium sulfate monohydrate. The long-term stabilized aqueous initiator composition may comprise at least about 0.01 wt. %, preferably at least about 0.05 wt. %, more preferably at least about 0.1 wt. %, and most preferably at least about 1.0 wt. %, from about 0.01 wt. % to about 25 wt. %, preferably from about 0.05 wt. % to about 20 wt. %, more preferably from about 0.1 wt. % to about 15 wt. %, and most preferably from about 1.0 wt. % to about 10 wt. % of the accelerator, based on the total weight of the long-term stabilized aqueous initiator composition.
[0045] The present long term stabilized aqueous initiator composition, which includes an initiator and a retarder, is in the aqueous phase, preferably in the form of a slurry or paste.
[0046] It is preferred that the pH value of the long term stabilized aqueous initiator composition is greater than 10, more preferably greater than 11, most preferably greater than 12, especially in the range of 10-14, preferably 11-13.
[0047] In a preferred embodiment, the long-term stabilized aqueous initiator composition comprises or consists of the following components: 45% to 85% by weight of calcium silicate cement, 0.01 to 0.5% by weight of sodium gluconate, and 10% to 35% water by weight.
[0048] In a most preferred embodiment, the long-term stabilized aqueous initiator composition comprises or consists of the following components: 45% to 85% by weight of C3S, which is free of aluminate clinker phase and free of lime, 0.01 to 0.5% by weight of sodium gluconate, and 10% to 35% water by weight.
[0049] The long-term stabilized aqueous initiator composition according to the present invention can be prepared as follows: calcium silicate cement and optionally fillers, thickeners, plasticizers are added to water while increasing the stirring speed until the mixture is homogenous. Finally, an optional accelerator component may be added until the mixture is completely homogenous. Thus, the method for preparing the long-term stabilized aqueous initiator composition according to the present invention comprises the following steps: i) introducing water into a mixing tank; ii) optionally dissolving and adding a thickener and optionally a plasticizer under stirring; iii) dissolving and adding calcium silicate cement and optionally fillers while increasing the stirring speed; vi) continuing the stirring until complete homogeneity is achieved.
[0050] The long-term stabilized aqueous initiator composition was stored in a closed container to avoid evaporation of water at ambient temperature and at 20° C. and evaluated for any changes in flowability, homogeneity (indicative of sedimentation) and pH value after several time intervals, i.e., 1 week, 4 weeks, 3 months, and 6 months. The properties of all components remained unaffected after 6 months, indicating a shelf life of at least 1 week, preferably at least 4 weeks, more preferably at least 3 months, and most preferably at least 6 months at ambient temperatures up to 20° C.
[0051] The long-term stabilized aqueous initiator composition can be used in a method for activating the setting and hardening of a cured aqueous phase aluminous cement component.
[0052] The method according to the invention comprises the steps of: i) adding the long-term stabilized aqueous initiator composition described above to the aqueous phase aluminous cement component; and ii) mixing the same.
[0053] Preferably, the cement component to which the long-term stabilization aqueous initiator composition can be added is based on aqueous phase calcium aluminate cement (CAC) or aqueous phase calcium sulfoaluminate cement (CAS). Calcium aluminate cements that can be used are characterized by rapid setting and hardening, rapid drying and shrinkage compensation when mixed with calcium sulfate, and excellent corrosion and shrinkage resistance. Such calcium aluminate cements suitable for use are, for example, Ternal® White (Kerneos, France).
[0054] In particular, the cement component may comprise at least about 40% by weight, preferably at least about 50% by weight, more preferably at least about 60% by weight, and most preferably at least about 70% by weight, from about 40% to about 95% by weight, preferably from about 50% to about 90% by weight, more preferably from about 60% to about 85% by weight, and most preferably from about 70% to about 80% by weight of calcium aluminate, based on the total weight of the cement component.
[0055] Alternatively, the cement component comprises at least about 20% by weight, preferably at least about 30% by weight, more preferably at least about 40% by weight, most preferably at least about 50% by weight, about 20% to about 80% by weight, preferably about 30% to about 70% by weight, more preferably about 35% to about 60% by weight, most preferably about 40% to about 55% by weight of alumina cement, and at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 15% by weight, most preferably at least about 20% by weight, about 1% to about 50% by weight, preferably about 5% to about 40% by weight, more preferably about 10% to about 30% by weight, most preferably about 15% to about 25% by weight of calcium sulfate, preferably calcium sulfate hemihydrate, based on the total weight of the cement component. The CaSO4 / CAC ratio of the cement component is 35:65 or less.
[0056] Preferably, the cement component is blocked with a blocking agent selected from the group consisting of boric acid, carboxylic acid, phosphoric acid, metaphosphoric acid, phosphorous acid, phosphonic acid, and salts thereof. The amount by weight of alumina cement and / or calcium sulfoaluminate cement relative to the total weight of the hydraulic binder is higher than any of the following values: 50%, 60%, 70%, 80%, 90%, 95%, 99% or is 100%.
[0057] The cement component may further comprise the following properties, either alone or in combination: Plasticizers that may be included in the cement component may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the families of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika® ViscoCrete®-20 HE (Sika, Germany). Suitable plasticizers are commercially available products.
[0058] The cement component may additionally comprise a thickening agent. Thickening agents that may be used may be selected from the group consisting of organic products such as xanthan gum, welan gum or DIUTAN® gum (CP Kelko, USA), mineral products such as starch-derived ethers, guar-derived ethers, polyacrylamides, carrageenan, agar, and clay, and mixtures thereof. Suitable thickening agents are commercially available products.
[0059] The cement component may further comprise an antimicrobial or biocide. Antimicrobial or biocide that may be used may be selected from the group consisting of compounds of the isothiazolinone family, such as methylisothiazolinone (MIT), octylisothiazolinone (OIT), and benzoisothiazolinone (BIT), and mixtures thereof. Suitable antimicrobial or biocide agents are commercially available products. Ecocide K35R (Progiven, France) and Nuosept OB 03 (Ashland, The Netherlands) are mentioned by way of example.
[0060] The cement component may also contain at least one filler, in particular an organic or mineral filler. Fillers that may be used may be selected from the group consisting of quartz powder, preferably quartz powder with an average particle size (d50%) of about 16 μm, silica sand, clay, fly ash, fumed silica, carbonate compounds, pigments, titanium dioxide, lightweight fillers, and mixtures thereof. Suitable mineral fillers are commercially available products. Quartz powder Millisil W12 or W6 (Quarzwerke GmbH, Germany) is mentioned by way of example.
[0061] The water content in the cement component may be at least about 1 wt%, preferably at least about 5 wt%, more preferably at least about 10 wt%, and most preferably at least about 20 wt%, from about 1 wt% to about 50 wt%, preferably from about 5 wt% to about 40 wt%, more preferably from about 10 wt% to about 30 wt%, and most preferably from about 15 wt% to about 25 wt%, based on the total weight of the cement component.
[0062] The presence of plasticizers, thickeners, and antimicrobial or biocides does not change the overall inorganic nature of the cement component.
[0063] Further, the cement component may include an accelerator component, which is composed of at least one alkali and / or alkaline earth metal salt selected from the group consisting of hydroxides, chlorides, sulfates, phosphates, monohydrogen phosphates, dihydrogen phosphates, nitrates, carbonates, and mixtures thereof, preferably the accelerator component is an alkali or alkaline earth metal salt, more preferably a water-soluble alkali or alkaline earth metal salt, more preferably a calcium metal salt such as calcium hydroxide, calcium sulfate, calcium carbonate, calcium chloride, calcium formate, or calcium phosphate, a sodium metal salt such as sodium hydroxide, sodium sulfate, sodium carbonate, sodium chloride, sodium formate, or sodium phosphate, or a lithium metal salt such as lithium hydroxide, lithium sulfate, lithium sulfate monohydrate, lithium carbonate, lithium chloride, lithium formate, or lithium phosphate, and most preferably lithium sulfate or lithium sulfate monohydrate. The cement component may contain at least about 0.01 wt. %, preferably at least about 0.05 wt. %, more preferably at least about 0.1 wt. %, and most preferably at least about 1.0 wt. %, from about 0.01 wt. % to about 25 wt. %, preferably from about 0.05 wt. % to about 20 wt. %, more preferably from about 0.1 wt. % to about 15 wt. %, and most preferably from about 1.0 wt. % to about 10 wt. % of the accelerator, based on the total weight of the cement component.
[0064] The cementitious components to which the present long term stabilized aqueous initiator composition may be added, including aluminous or calcium sulfoaluminate cements, are preferably present in the aqueous phase, most preferably in the form of a slurry or paste.
[0065] The long-term stabilizing aqueous initiator composition according to the invention is used in a mortar system containing a cured aqueous phase alumina cement component. In particular, the long-term stabilizing aqueous initiator composition is used as the first component in a two-component mortar system containing a cured aqueous phase alumina cement component. Preferably, the use of the long-term stabilizing aqueous initiator composition according to the invention results in a two-component mortar system having an initial setting time of at least 5 minutes.
[0066] In particular, the long-term stabilized aqueous initiator composition according to the invention is used to activate the setting and hardening of cured aqueous phase aluminous cement components used for chemically fixing an anchoring means in a mineral substrate. Preferably, the anchoring means is an anchor rod, a threaded anchor rod, a bolt or a steel reinforcement. The mineral substrate to which the anchoring means is chemically fixed is a structure made of brickwork, concrete, permeable concrete or natural stone.
[0067] Furthermore, the long-term stabilized aqueous initiator composition according to the invention may be used in inorganic mortar systems as a coating or for the attachment of fibres, scrims, fabrics or composites, in particular high modulus fibres, preferably carbon fibres, in particular for the reinforcement of building structures, e.g. walls or ceilings or floors, or even for the installation of components, such as plates or blocks made of stone, glass or plastic, on building or structural elements.
[0068] The following examples illustrate the invention without, however, limiting it thereto. EXAMPLES
[0069] 1. Preparation of long-term stable aqueous initiator composition and thermal output measurement The present long-term stabilized aqueous initiator composition is formed by first mixing together the siliceous clinker phase, the blocking agent, and water.
[0070] The heat output associated with the hydration of the siliceous clinker phases tricalcium silicate (C3S, monoclinic) and dicalcium silicate (α'-C2S and β-C2S) was measured using an 8-channel TA Instruments TAMair calorimeter. For each measurement, always 3 g of clinker phase (C3S, α'-C2S or β-C2S) was mixed with 1.2 g of deionized water (water / cement ratio = 0.4). The resulting paste was placed in a glass vial, sealed and lowered into the apparatus to measure the heat output during the exothermic hydration of the cement for up to 7 days. All clinker phases were hydrated at 400 cm 2 The powder was ground to a Blaine fineness of 1 / g.
[0071] To measure the effectiveness of the identified blocking agents, they were weighed out in amounts of either 0.1, 0.2 or 0.3% bwoc (by weight of the respective siliceous clinker phase). In a first step, the blocking agents were dissolved in deionized water. In a second step, a paste was prepared with the charged water, maintaining a water / cement ratio of 0.4. Any traces of reactivity during the first few days of the reaction were followed by calorimetry. If no heat output was recorded, the reaction was considered to be successfully blocked.
[0072] Additionally, the effectiveness of the blocking agent was evaluated over a period of 150 days. 10 g of paste loaded with blocking agent was prepared as detailed above and sealed in a glass vial. The paste was evaluated at regular intervals and the time at which the paste hardened was recorded.
[0073] Comparative example: Thermal output measurement of an unblocked siliceous clinker phase The heat output of the pure clinker phases reacting in water is summarized in Table 1. Comparative Example 1 (C3S) shows the highest heat output (150.8 J / g) already in 1 day. The dicalcium silicate clinker phases show a much lower heat output, releasing only 43.6 and 36.0 J / g for the α' and β polymorphs, respectively.
[0074] [Table 1]
[0075] Example of the invention: Thermal output measurements of siliceous clinker phases with different amounts of blocking agent Table 2 reveals the total heat output of C3S and C2S charged with various amounts of sodium gluconate. The heat output remains low at about 10 J / g for all clinker phases investigated and all concentrations tested. This heat output is a result of the sample chamber being exposed to room temperature when the sample was introduced (as seen by the 10 min data point). At the end of the 7 days, all pastes prepared were still hand mixable.
[0076] [Table 2]
[0077] Example of the invention: Heat output of siliceous clinker phase tricalcium silicate with different blocking agents Several blocking agents were identified and tested to rank their effectiveness in blocking the hydration of C3S, the results of which are detailed in Table 3. Of all the blocking agents tested, sodium gluconate, glucose, phosphonates, and glycolic acid were all successful in blocking the hydration of tricalcium silicate C3S for at least 7 days, e.g., low power outputs were measured and the paste was still able to mix. However, lignosulfonates and phosphates only delayed the hydration of the clinker phase.
[0078] [Table 3]
[0079] Long-term blocking of C3S For all blocking agents tested, increasing their concentration relative to the amount of clinker typically increased the blocking time, except for glycolic acid. For the same concentration of blocking agent fixed at 0.3 wt.% of clinker, sodium gluconate, glucose, and phosphonates were able to block hydration for at least 3 months. In pastes prepared with 1 wt.% of blocking agent of clinker, using glucose and lignosulfonate, the paste did not harden in 150 days. The paste prepared with phosphonate hardened after 120 days.
[0080] [Table 4]
[0081] Long-term blocking of C2S The effectiveness of blocking agents for α'-C2S and β-C2S is shown in Tables 5 and 6. For α'-C2S, sodium gluconate, glucose, and phosphonate were very effective in blocking hydration, and no hardening of the paste was observed in the first 3 months.
[0082] [Table 5]
[0083] [Table 6]
[0084] For C3S, glucose, lignosulfonate, and sodium gluconate were the most effective blocking agents. At 1% dosage, lignosulfonate and sodium gluconate effectively stopped the reaction for 150 days. For α'-C2S, extensive blocking could be achieved at a concentration of 0.3% by weight of clinker when using sodium gluconate, glucose, and phosphonates. For β-C2S, extensive blocking could be achieved at a concentration of 0.3% by weight of clinker when using glucose and phosphonates.
[0085] 2. Stability monitoring of long-term stabilized aqueous initiator compositions The long-term stabilized aqueous initiator composition was stored in a closed container to avoid evaporation of water at ambient temperature and 20° C. and evaluated for any changes in flowability, homogeneity, and pH value after several time intervals, i.e., 1 week, 4 weeks, 3 months, and 6 months. The initiation ability was also tested.
[0086] Measuring the pH value is a good way to monitor the stability of an aqueous composition, i.e., a suspension. The present long-term stabilized aqueous initiator composition is considered unstable if its pH value changes significantly.
[0087] The homogeneity assessment is a good way to monitor the stability of an aqueous composition, i.e., a suspension. The long-term stabilized aqueous initiator composition is considered unstable if it begins to harden and settle. The homogeneity assessment is used as an indicator of settling.
[0088] The properties of the aqueous initiator composition of the invention, in particular the properties of all components, remained unaffected after 6 months, so that the shelf life is at least 6 months at ambient temperature and at a temperature of 20° C. The pH value remained above 12. The initiation ability remained intact compared to freshly produced components.
[0089] 3. Start of curing type aqueous alumina cement component The initiation ability of the long-term stabilized aqueous initiator compositions of the present invention was evaluated by activating the setting and hardening of the cured aqueous phase alumina cement component, which includes adding the long-term stabilized aqueous initiator compositions B1 and B2 to the aqueous phase alumina cement component (composition A, Table 7) and mixing it.
[0090] The aqueous phase aluminous cement component (A) is prepared by first mixing the components specified in Table 7. The percentages given are expressed as weight percent.
[0091] Specifically, 19.86 grams of deionized water, 0.75 grams of 85% phosphoric acid (blocking agent), 0.6 grams of Ethacryl G (superplasticizer), and 0.015 grams of Nuosept® (biocide) were homogenized at room temperature, and calcium aluminate cement (78.28 grams, pure Ternal White®) was added in small portions one after another while stirring with a dissolver, finally obtaining a smooth liquid paste-like slurry of blocked cement in water with a pH of less than 7. After the calcium aluminate cement was added, 0.5 grams of xanthan gum (thickener) was added, and the slurry was homogenized at 2000 rpm for 5 minutes.
[0092] [Table 7]
[0093] An exemplary preparation of component B is as follows: Tricalcium silicate (CS), water, and sodium gluconate were mixed and homogenized. The pH of the blocked silicate slurry was about 12.
[0094] [Table 8]
[0095] Calorimetric Observation Mixtures of silicate and aluminate mortars were prepared with varying C3S / CA ratios according to Table 3. Extra water was added to fix the water / (C3S+CA) ratio at 0.4 and the mortars were mechanically mixed in a high speed mixer. The details of the mixtures, the weight ratios of the two slurries A:B and their overall C3S:CAC ratios are given in Table 9.
[0096] [Table 9]
[0097] The possibility of reactivating the cement binder by combining the two blocked systems is measured by the heat output of hydration. The dissolution of the clinker phase is exothermic and measuring the heat output is favorable to follow the hydration. All the masses were hard by the end of the test (7 days), indicating that they can be used for fixing of anchoring means. The heat outputs are summarized in Table 10.
[0098] [Table 10]
[0099] Table 10 shows the effect of the blocking agent (sodium gluconate) dosage on the total heat output of the C3S-rich blends. Comparing Example 3 with Example 5 and Example 4 with Example 6 for a fixed C3S / CAC ratio, it can already be seen that increasing the amount of blocking agent reduces the heat output by the seventh day of hydration, meaning that less reaction has occurred during that period, lowering the loading values at early ages. Comparing Example 3 with Example 4 and Example 5 with Example 6 for a fixed blocking agent / C3S ratio, increasing the C3S fraction in the system reduces the heat output of the mortar. However, the heat increases and the mass hardens.
[0100] The heat output of mortars with blends varying the ratio of C3S to CAC, varying the C3S in the blends from 85% to 15%, is also shown in Table 10. For blends containing 85% C3S, the lowest heat output was recorded by day 7. When the C3S fraction was replaced by calcium aluminate fraction, the heat output increased continuously by day 7.
[0101] The addition of the aqueous initiator composition of the present invention to the aqueous phase aluminous cement component resulted in a mortar system having an initial setting time of at least 5 minutes, particularly in the range of about 5 to 25 minutes.
[0102] The aqueous initiator composition of the present invention has been shown to have a long life, i.e., shelf life, i.e., the aqueous initiator composition does not congeal at ambient temperature for a period ranging from several weeks to several months, i.e., at least one week, preferably at least four weeks, more preferably at least three months, and most preferably at least six months, when stored at ambient temperature, and is thus protected from any storage or delivery delays. The aqueous initiator composition of the present invention remains in a slurry state and does not separate, especially during transportation, so that on-site implementation can be guaranteed. Furthermore, the composition has low toxicity and ecotoxicity.
[0103] When the cured aqueous phase aluminous cement component is initiated with the aqueous initiator composition of the present invention, it provides a curing rate and therefore mechanical strength comparable to organic systems, but its essentially mineral composition makes it much less toxic than known systems of the prior art, much less polluting to the environment and allowing for cost-effective production.
[0104] Furthermore, it has been shown that aqueous slurry-based systems containing a blocked alumina component as the primary binder component and a blocked calcium silicate cement in an aqueous slurry exhibiting an alkaline pH as the secondary binder component can utilize lower water-to-cement ratios compared to state-of-the-art two-component pourable mortars containing a filler-based activator component. Additionally, it has been shown that the long-term strength loss due to conversion characteristic of calcium aluminate cements can be mitigated by blending these two cements to produce stable hydrates of calcium silicate hydrate and portlandite phases.
[0105] Furthermore, it has been shown that the mortar system comprising the aqueous initiator composition of the present invention does not contain any harmful substances while maintaining the standards for chemical bonding applications, thus encompassing reduced labeling.
Claims
1. A long-term stabilized aqueous initiator composition comprising a blocked calcium silicate cement and water.
2. 2. The long-term stabilized aqueous initiator composition of claim 1, wherein the blocked calcium silicate cement comprises a calcium silicate cement and the blocking agent for the calcium silicate cement is selected from the group consisting of monosaccharides, carboxylic acids, gluconic acid, glycolic acid, lignosulfonates, phosphoric and phosphonic acids, their salts and esters, glucose, and mixtures thereof.
3. 3. The long-term stabilized aqueous initiator composition of claim 2, wherein the calcium silicate cement is present in a range of about 10% by weight to about 90% by weight, based on the total weight of the long-term stabilized aqueous initiator composition.
4. 4. The long-term stabilized aqueous initiator composition according to claim 2 or 3, wherein the blocking agent for the calcium silicate cement is present in a range of about 0.01 wt.% to about 10 wt.%, based on the total weight of the long-term stabilized aqueous initiator composition.
5. The long-term stabilized aqueous initiator composition of any one of claims 2 to 4, wherein the blocking agent is sodium gluconate.
6. The calcium silicate cement is a siliceous clinker phase tricalcium silicate C 3 S, dicalcium silicate C 2 6. The long-term stabilized aqueous initiator composition of claim 2, further comprising:
7. The calcium silicate cement is free of aluminate clinker phase and free of lime, most preferably free of aluminate clinker phase and free of lime. 3 7. The long-term stabilized aqueous initiator composition of claim 2, wherein
8. 8. The long term stabilized aqueous initiator composition of any one of claims 1 to 7, wherein the aqueous initiator composition has a shelf life of at least six months.
9. The long-term stabilized aqueous initiator composition of any one of claims 1 to 8, wherein the aqueous initiator composition is in the form of a slurry or paste.
10. 10. The long-term stabilized aqueous initiator composition of any one of claims 1 to 9, wherein the aqueous initiator composition has a pH value of greater than 10.
11. The aqueous initiator composition comprises: 45% to 85% by weight of C, free of aluminate clinker phase and free of lime 3 S. and 0.01 to 0.5% by weight of sodium gluconate; 11. The long-term stabilized aqueous initiator composition of any one of claims 1 to 10, comprising 10% to 35% by weight of water.
12. A method for preparing a long-term stabilized aqueous initiator composition according to any one of claims 1 to 11, comprising the steps of: i) adding the long-term stabilized aqueous initiator composition described above to the aqueous phase alumina cement component; and ii) mixing thereof.
13. 1. A method for activating the setting and hardening of a cured aqueous phase aluminous cement component, comprising: i) introducing water into a mixing tank; ii) dissolving and adding calcium silicate cement and optionally fillers while increasing the stirring speed; iii) continuing the stirring until complete homogeneity.
14. Use of the long-term stabilizing aqueous initiator composition according to any one of claims 1 to 11 in a mortar system containing a cured aqueous phase aluminous cement component.
15. Use of the long-term stabilized aqueous initiator composition according to any one of claims 1 to 11 as a first component in a two-component mortar system comprising a cured aqueous phase aluminous cement component.
16. 16. The use according to claim 15, wherein the two-component mortar system has an initial setting time of at least 5 minutes.
17. Use of a long-term stabilized aqueous initiator composition according to any one of claims 1 to 11 for activating the setting and hardening of a cured aqueous phase aluminous cement component used for chemically fixing an anchoring means in a mineral substrate.
Citation Information
Patent Citations
High temperature resistant water polystyrene material
CN109320153A
Aluminate and Portland cement-based double-liquid grouting material and preparation method thereof
CN113816701A
Reactivatable congelation-controlled cementitious composition
JP1983115052A
Adjusting method for coagulating hardening cement kneaded matter
JP1997254136A
Cement admixture and cement composition
JP2004137091A